Ctenophore relationships and their placement as the sister group to all other animals. Issue 11 (November 2017) - Whelan, Nathan; Kocot, Kevin; Moroz, Tatiana; Mukherjee, Krishanu; Williams, Peter; Paulay, Gustav; Moroz, Leonid; Halanych, Kenneth
Abstract Ctenophora, comprising approximately 200 described species, is an important lineage for understanding metazoan evolution and is of great ecological and economic importance. Ctenophore diversity includes species with unique colloblasts used for prey capture, smooth and striated muscles, benthic and pelagic lifestyles, and locomotion with ciliated paddles or muscular propulsion. However, the ancestral states of traits are debated and relationships among many lineages are unresolved. Here, using 27 newly sequenced ctenophore transcriptomes, publicly available data and methods to control systematic error, we establish the placement of Ctenophora as the sister group to all other animals and refine the phylogenetic relationships within ctenophores. Molecular clock analyses suggest modern ctenophore diversity originated approximately 350 million years ago ± 88 million years, conflicting with previous hypotheses, which suggest it originated approximately 65 million years ago. We recoverEuplokamis dunlapae —a species with striated muscles—as the sister lineage to other sampled ctenophores. Ancestral state reconstruction shows that the most recent common ancestor of extant ctenophores was pelagic, possessed tentacles, was bioluminescent and did not have separate sexes. Our results imply at least two transitions from a pelagic to benthic lifestyle within Ctenophora, suggesting that such transitions were more common in animal diversification than previously thought. Newly sequenced transcriptomes are combined with existing data to establish Ctenophora as the sister group to all other animals and suggest a radiation around 350 Ma as well as multiple transitions from a pelagic to a benthic lifestyle.